Do different pretreatments of dentine surface affect the bond strength with a self-adhesive resin cement? - de Oliveira Reis, Bruna [UNESP]; de Lima Godas, André Gustavo [UNESP]; Suzuki, Thaís Yumi Umeda; Fagundes, Ticiane Cestari [UNESP]; Briso, André Luiz Fraga [UNESP]; Santos, Paulo Henrique dos [UNESP] (My University, 2020)
Purpose: To evaluate the microtensile bond strength of dentine/self-adhesive resin cement interface after several treatments on a dentine surface. Materials and Methods: Twenty-eight human molars were selected and divided into four groups: no treatment (control (C); 2% chlorhexidine digluconate (CHX); 25% polyacrylic acid (PA); and 23 ppm dispersive solution of silver nanoparticle (SN). Prepolymerised TPH resin composite (Dentsply) blocks were luted on the dentine surface using RelyX U200 self-adhesive resin cement (3M ESPE). Microtensile bond strength was measured (MPa) in a universal testing machine 24 h and 6 months after the bonding process. The fractured specimens were examined in an optical microscope and classified according to the fracture pattern. A representative sample of each group was observed by scanning electronic microscope. Data were submitted to analysis of variance (ANOVA) and Tukey's test to compare the mean among the groups (p <0.05). Results: The highest microtensile bond strength values after 24 h were found for the PA group (13.34 ± 6.36 MPa), with no statistically significant difference for the C group (9.76 ± 3.11 Mpa). After 6 months, the highest microtensile bond strength values were found for the C group (9.09 ± 3.27 Mpa), with statistically significant difference only for the CHX group (2.94 ± 1.66 MPa). There was statistically significant difference only for the PA group when comparing the periods studied. Regardless of the surface treatment applied, there were more adhesive failures in both periods of time. Conclusion: Dentinal pretreatment with PA, as well as use of SN before the bonding procedure of self-adhesive resin cement to dentine, may be alternative bonding protocols.
Keywords: Dentine-bonding agents; Resin cements; Tensile strength